Integrasi Artificial Intelligence dalam Pendidikan Fisika dan Matematika Berbasis Nilai-Nilai Al-Qur’an Era Tranformasi Digitalisasi - Muhammad Ikhsan; Muhammad Amin Badali; Ferdianur Ferdianur; Muhammad Nabil Wahyu Hidayat; Amin Nasrullah (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
The integration of Artificial Intelligence (AI) in Physics and Mathematics education has become a strategic necessity in the era of digital transformation. However, the use of advanced technology without a strong value foundation may lead to ethical and spiritual degradation among learners. This study aims to comprehensively examine the concept, models, and challenges of integrating AI in Physics and Mathematics learning based on Qur’anic values. This research employs a library research method with a thematic content analysis approach, drawing on recent and relevant scholarly sources. The findings indicate that AI has significant potential to enhance learning effectiveness through adaptive learning systems, digital simulations, and objective automated assessments. In the context of Physics and Mathematics, AI facilitates the visualization of abstract concepts, strengthens conceptual understanding, and develops students’ logical and systematic thinking skills. The integration of Qur’anic values serves as a spiritual foundation that guides the use of AI in alignment with principles of monotheism, ethics, and moral responsibility. These values reinforce the understanding that science and technology function as means to recognize divine order and foster ethical awareness. This study concludes that AI integration grounded in Qur’anic values can support holistic education that is academically excellent, digitally adaptive, and spiritually grounded, provided that adequate infrastructure, qualified human resources, and value-based educational policies are in place to support it. Keywords: Artificial Intelligence, Physics Education, Mathematics Education, Qur’anic Values, Digital Transformation.